Surgical management of spontaneous vitreous hemorrhage, presumably of rhegmatogenous origin - D. O. Shkvorchenko; E. S. Khrisanfova; S. A. Kakunina; A. S. Zhuravlev; D. G. Uzunyan (Офтальмохирургия, 2022)
Relevance. There are many causes of spontaneous hemorrhage into the vitreous cavity. Sometimes spontaneous nontraumatic vitreous hemorrhage can be rhegmatogenous in nature, occurring as a result of a ruptured retinal vessel running through the site of a retinal tear. Usually, a patient with spontaneous nontraumatic vitreous hemorrhage is managed with a conservative approach, but it is questionable whether conservative management of patients with this pathology is advisable. Purpose. To evaluate the results of surgical treatment of patients with idiopathic, presumably rhegmatogenous vitreous hemorrhage. Material and methods. Surgical treatment of 10 patients diagnosed with idiopathic vitreous hemorrhage, presumably of rhegmatogenous nature, was performed and the results of treatment were evaluated. The best corrected visual acuity (BCVA) before treatment was on average 0.03. Slit lamp examination revealed dispersed vitreous hemorrhage into the vitreous body with a total obscuration of the posterior pole. According to B-scan data there was no retinal detachment in all cases. All patients underwent surgical treatment. Results. By the third month of follow-up after surgical treatment, visual acuity was 0.9±0.04 on average. B-scan data showed no pathology in all cases. Light sensitivity was 28.7±0.15 dB on average. Conclusion. If other obvious causes of vitreous hemorrhage are excluded, urgent surgical treatment is, in our opinion, the most preferable approach and can be recommended as a first line of treatment instead of conservative therapy